Analysis of Host and Socio-Economic Factors as Risk Factors for Stunting in Toddlers in the Working Area of the Kesesi II Health Center, Pekalongan Regency, Indonesia - Maulana, Jaya; Siti Aisah; Suwondo (Open Access Indonesian Journal of Medical Reviews, 2023)
Stunting or failure to thrive causes difficulties for toddlers in achieving optimal physical and cognitive development. Kesesi District is in first place and the Kesesi II Health Center as of February 2023 still has a high stunting rate, namely 165 cases. This study aimed to analyze host factors as risk factors for stunting in toddlers in the working area of the Kesesi II Health Center. This research is an analytical research with a quantitative approach and a case control research design. From the Chi-square test, the results of the maternal pregnancy history were obtained (p-value = 0.000, OR = 6.089, 95% CI = 2.146 - 17.276) history of infectious diseases in toddlers (p-value = 0.000, OR = 8.516, CI 2.953 - 24.561), history of exclusive breastfeeding (p-value = 0.021, OR = 3.478, 95% CI = 1.172 - 10.323), history of LBW (p-value = 0.000, OR = 10.500, 95% CI 3.628 - 30.392), family economic status ( p-value = 0.287, OR = 2.188, 95% CI = 0.505 - 9.480). This study shows that the mother's history of pregnancy, history of infectious diseases, history of exclusive breastfeeding, and history of LBW are host factors that are at risk for the incidence of stunting in toddlers in the Kesesi II Health Center working area in 2023.